2014
DOI: 10.3747/pdi.2013.00001
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Serum-Intact Parathyroid Hormone, Serum 25-Hydroxyvitamin D. Oral Vitamin D Analogs and Metabolic Syndrome in Peritoneal Dialysis Patients: A Multi-Center Cross-Sectional Study

Abstract: M etabolic syndrome (MS) consists of a cluster of metabolic and hemodynamic abnormalities. The components of MS such as abdominal obesity, high blood pressure, insulin resistance and dyslipidemia are risk factors for chronic kidney disease (CKD) (1,2), diabetes (3), cardiovascular disease (4) and high cardiovascular mortality (5). on the other hand, the components of MS develop early in CKD and are exacerbated during the progression to end-stage renal disease (eSRD) (6,7). The prevalence of MS is remarkably hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
(88 reference statements)
1
16
0
Order By: Relevance
“…Consistent with a previous study, vitamin D deficiency was found to be prevalent in a significant proportion of PD patients [ 26 , 27 ]. The possible reasons of high prevalence of vitamin D dificiency include chronic renal failure, dietary restrictions, loss of vitamin D in the peritoneal effluent and decreased exposure to sunlight [ 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with a previous study, vitamin D deficiency was found to be prevalent in a significant proportion of PD patients [ 26 , 27 ]. The possible reasons of high prevalence of vitamin D dificiency include chronic renal failure, dietary restrictions, loss of vitamin D in the peritoneal effluent and decreased exposure to sunlight [ 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…Szeto et al [15] compared the prevalence of MS in a single center in Hong Kong with 329 prevalent patients, including 31% of diabetics, and noted that the prevalence rates ranged from 53% to 66%, with higher prevalence according to the modified NCEP-ATPIII and then followed by the NCEP-ATPIII. Dong et al [16] found that the prevalence of MS in China from a multicenter study involving 4 different regions of China including 40% of diabetics was 55.4% according to NCEP-ATPIII. If diabetics are excluded, it is expected that the prevalence should be lower.…”
Section: Prevalence Of Ms In Pd Patientsmentioning
confidence: 99%
“…Serum iPTH is positively correlated with the risk of MS. 3336 However, the opposite trend was reported by Dong et al. among Chinese patients undergoing PD 3 in a large, multi-center, cross-sectional study. Here, we found the same trend of negative correlation between serum iPTH and MS among our patients receiving PD (patients with MS: 42.0 ± 42.7 pmol/L; patients without MS: 53.9 ± 51.9 pmol/L), although the difference was not significant.…”
Section: Discussionmentioning
confidence: 85%
“…As expected, this prevalence varies by ethnicity, geographical region, and the different definitions used. [1][2][3][4] MS refers to a constellation of several risk factors for cardiovascular disease (CVD), type II diabetes, systemic inflammation, and the development of chronic kidney disease (CKD). Among them, CVD is the leading cause of death in patients with ESRD under long-term PD treatment.…”
Section: Introductionmentioning
confidence: 99%